A synthesis of research on deaf and hearing children's mathematical achievement - Gottardis, L; Nunes, T; Lunt, I (2011)
Over five decades, researchers have reported that deaf children lag behind their hearing peers on different educational measures. This review aims to synthesize the information on the nature and extent of this delay. A systematic search of the literature comparing deaf and hearing children's performance in mathematics was carried out. Of the 23 relevant articles, 13 employed standardized measures and 10 used un-standardized measures. The analysis demonstrates that, for children whose level of hearing loss is greater than moderate, there is a delay in mathematics in comparison with hearing children. This delay is noted in all assessments with standardized measures. Three studies (about 30%) that used un-standardized measures reported no delay; in these studies the children did not have to use conventional mathematical signs in order to solve the tasks. This may indicate that deaf children's number representation is not impaired but their learning of conventional mathematical signs is delayed. An attempt was made to quantify the level of delay, but the findings must be interpreted with caution due to possible confounding in the studies, some related to the sample (inclusion and exclusion criteria) and others related to the lack of controls (comparisons with only chronologically age-matched controls when general intelligence should have been controlled for). © W.S. Maney and Son Ltd 2011.